VDC_100102371237.0X000001. Issue 10 (October 2018) - Tom, Cynthia M.; Won, Roy P.; Friedlander, Scott; Sakai-Bizmark, Rie; Virgilio, Christian De; Lee, Steven L.
Variations in the management of adolescents at children's hospitals (CHs) and nonchildren's hospitals (NCHs) have been well described in the trauma literature. However, the effects of CH designation on outcomes after common general surgical procedures have not been investigated. The purpose of this study was to compare the outcomes and costs of adolescent cholecystectomies performed at CHs and NCHs. Within the California State Inpatient Database (2005–2011), we identified 8117 cholecystectomy patients aged 13 to 18 years at CHs and NCHs. Outcomes (laparoscopy, intraoperative cholangiogram, length of stay (LOS), and complications) and costs were analyzed. CHs cared for younger patients, more uninsured patients, and more black patients. NCHs were associated with higher laparoscopy use (95.7% vs 88.3%, P < 0.01), higher intra-operative cholangiogram rates (28.8% vs 11.9%, P < 0.001), shorter LOS (3.2 vs 5.0 days, P < 0.01), and lower costs by $5797 per patient ($11, 219 vs $17, 016, P < 0.01). Although there was no significant difference in overall complication rates, CHs had higher rates of infectious complications (2.0% vs 1.0%, P = 0.004). Adolescent cholecystectomies are safely performed at NCHs while achieving increased laparoscopy use, shorter LOS, and lower costs compared with CHs.